2013
DOI: 10.3390/medicina49100069
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-Stretching Based on Postisometrical Relaxation, Static Stretching Combined with Stabilizing Exercises, and Stabilizing Exercises Only on the Flexibility of One-Joint and Two-Joint Hip Flexors

Abstract: Background and Objective. The limitations of muscle flexibility are a common dysfunction of the musculoskeletal system. Therefore, various therapeutic techniques are used in rehabilitation programs to increase their flexibility. The aim of this prospective, randomized, single-blind study was to evaluate the changes in the flexibility of hip flexors in children who participated in a 6-week therapeutic program consisting of one physiotherapy session per week with a physiotherapist and daily home exercises. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies have been conducted in which authors investigated the efficacy of hip extension strengthening and stretching of the hip flexors on lumbar hyperlordosis in adults (Oh et al, 2007;Malai et al, 2015). In another study, the authors established the efficacy of hip flexors and functional stretching exercises on hyperlordosis in infants (Czaprowski et al, 2013). To the best of researcher's knowledge, no studies were found on the various methods and approaches to correct hyperlordosis in children with diplegic CP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been conducted in which authors investigated the efficacy of hip extension strengthening and stretching of the hip flexors on lumbar hyperlordosis in adults (Oh et al, 2007;Malai et al, 2015). In another study, the authors established the efficacy of hip flexors and functional stretching exercises on hyperlordosis in infants (Czaprowski et al, 2013). To the best of researcher's knowledge, no studies were found on the various methods and approaches to correct hyperlordosis in children with diplegic CP.…”
Section: Introductionmentioning
confidence: 99%